2004
DOI: 10.1103/physrevc.69.044318
|View full text |Cite
|
Sign up to set email alerts
|

Evidence forαclustering in heavy and superheavy nuclei

Abstract: We analyze the ␣ decay between ground states along N − Z chains in deformed heavy and superheavy nuclei, by using the pairing approach. We show that the derivative of the preformation amplitude is practically a constant along any ␣ chain, while that of the outgoing wave function changes exponentially upon the Coulomb parameter. This leads to the breakdown of the continuity equation and therefore to wrong decay widths. The behavior cannot be explained within the standard shell model. We significantly correct th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(45 citation statements)
references
References 52 publications
1
44
0
Order By: Relevance
“…For the case of higher-multipole deformations included [the (β 2i , β 3i , β 4i ) case, showing the best fit to T 1/2 data], P 0 for 14 C lies in the range of 2.21 × 10 −15 to 4.55 × 10 −19 , which is smaller, though, than the predicted values of many other models [11,16,[19][20][21], including the first estimate of Rose and Jones [5] for the calculated P 0 (α) values of, say, Refs. [34,36]. However, P 0 in the PCM of Gupta and collaborators is a relative quantity, and its value depends on the choice of Half-lives log 10 T 1/2 (s) nuclear part of the potential in the fragmentation potential V (η), just as the P value would depend on the chosen nuclear potential in the scattering potential V (R).…”
Section: Calculations and Discussionmentioning
confidence: 96%
“…For the case of higher-multipole deformations included [the (β 2i , β 3i , β 4i ) case, showing the best fit to T 1/2 data], P 0 for 14 C lies in the range of 2.21 × 10 −15 to 4.55 × 10 −19 , which is smaller, though, than the predicted values of many other models [11,16,[19][20][21], including the first estimate of Rose and Jones [5] for the calculated P 0 (α) values of, say, Refs. [34,36]. However, P 0 in the PCM of Gupta and collaborators is a relative quantity, and its value depends on the choice of Half-lives log 10 T 1/2 (s) nuclear part of the potential in the fragmentation potential V (η), just as the P value would depend on the chosen nuclear potential in the scattering potential V (R).…”
Section: Calculations and Discussionmentioning
confidence: 96%
“…The global calculation of α-decay half-lives presented in this article should be useful in future studies of α-decay half-lives of medium and heavy nuclei far from stability and for those of superheavy elements. Finally, we would like to mention that there are other approaches to the study of α-decay of deformed nuclei [46][47][48]. Fröman [46] investigated α decay with the deformed WKB approach, and this was further developed by Delion et al [47].…”
Section: Superheavy Nucleimentioning
confidence: 98%
“…But the penetration factor P varies significantly when the deformation effect of the daughter nucleus is taken into account. So the penetration factor is more sensitive to nuclear deformation than to other terms of the decay width [46][47][48][49]. It is thus concluded that nuclear deformation mainly affects the barrier penetration probability of the α particle.…”
Section: B Variation Of Each Term In Deformed Ddcmmentioning
confidence: 99%
“…(6) is obviously a quite simple approximation for the description of the complex many-body wave function of a superheavy nucleus which was analyzed e.g. in [32,33,34,35,36]. Nevertheless, the preformation factor defined as ratio P = T calc 1/2,α /T exp 1/2,α in Eq.…”
mentioning
confidence: 99%